Avaliação de empresas start-ups: abordagem tradicional x opções reais - Bicudo, Luis Filipi Bouyer (2016)
The aim of this study is to compare the two methodologies of company’s valuation, discounted cash flow and real options for a start-up company. Due to the difficulties of estimating the value of a company through the assumptions made, when it is a start-up, the lack of historical and market evidence, the work becomes even more subjective. The importance of having a more accurate method and consider the many variables inherent in a company that proposes to act in an untapped market and innovate to solve an identified problem is essential to encourage entrepreneurship, a key issue to boost an economy. A case study was prepared with a Brazilian start-up, which operates in the food industry, with more than four years of operation and has received investment from angel investors and venture capital fund. Through technology, the company seek to innovate in the gastronomical experience of the customer and partner restaurants. The company's board released the company's internal data and future projections. The methodology of discounted cash flow was applied to estimate the value of the start-up and then was applied the real option methodology by adding an expansion option and a drop one to estimate another value for the company in various scenarios with different volatilities. The result shows a considerable difference between the methodology, in which the method of real options increases the company's value in all scenarios.